ICNP® Diagnoses of People Living with AIDS, and Empirical Indicators - Vinicius Lino de Souza Neto; Rayane Teresa da Silva Costa; Danyella Augusto Rosendo da Silva Costa; Sâmara Sirdênia Duarte de Rosário Belmiro; Maria Alzete de Lima; Richardson Augusto Rosendo da Silva
ABSTRACT Objective: To analyze the association between the empirical indicators and ICNP® nursing diagnoses in people living with AIDS, as well as to identify the predictive indicators for the establishment of these diagnoses. Method: A cross-sectional study with 120 people living with AIDS, in a hospital in Northeastern Brazil, conducted from August to September 2015, following the steps: identification and validation of Empirical Indicators; preparation and validation of the ICNP® Nursing Diagnoses; and analysis of the association between the Empirical Indicators and the Nursing Diagnoses resulting from the two previous steps. To analyze the data, we used logistic regression. Results: 74 Empirical Indicators were identified, being 31 of which were validated. 55 diagnoses were elaborated and 19 were validated, of which 16 were associated with the Empirical Indicators, identifying 31 predictors. Conclusion: The diagnoses presented significant associations with the Empirical Indicators. In addition, it was observed that the predictive factors of these diagnoses involved the human responses and complications related to the disease, which should be considered during the care provided by the nurse.